Oil rents and economic growth in oil producing countries: evidence from a macro panel - Fuinhas, José Alberto (2019)
In this paper, new approaches are taken to explore two new dimensions of the oil growth nexus that are relevant when focusing on oil producing countries. Based on panel regressions, we regress per capita income on the ratio of oil production to primary energy consumption and oil rents per capita, adding control variables and exploring a relationship analysis within a multivariate oil-growth nexus framework. The per capita oil consumption-economic growth nexus is examined in a panel of oil producing countries over a long time span (1970–2012), controlling for the exports of goods and services, the ratio of oil production to primary energy consumption, the oil rents, and international crude oil prices. The phenomenon of cross-sectional dependence that is present in the panel confirms that these countries share common spatial patterns, unobserved common factors, or both. The cointegration/long memory relationships, as well as the panel data estimators’ appropriateness, are both analysed and discussed. A dynamic Driscoll-Kraay estimator, with fixed effects, is shown to be adequate to cope with the phenomena of heteroskedasticity, contemporaneous correlation, first order autocorrelation and cross-sectional dependence, present in the panel. Oil consumption drives economic growth, but only on the short-run. The ratio of oil production to primary energy consumption has exerted a positive impact on growth in both the short- and longrun. Oil prices only exert a positive effect on growth in the short-run. Oil rents depress growth in both the short- and long-run, suggesting that it is more a curse than a blessing for the economies.